Loss of Prune in Circadian Cells Decreases the Amplitude of the Circadian Locomotor Rhythm in Drosophila - Chen, Wenfeng; Xue, Yongbo; Scarfe, Lisa; Wang, Danfeng; Zhang, Yong (Frontiers in Cellular Neuroscience, 2019)
The circadian system, which has a period of about 24 hours, is import for organismal health and fitness. The molecular circadian clock consists of feedback loops involving both transcription and translation, and proper function of the circadian system also requires communication among intracellular organelles. As important hubs for signaling in the cell, mitochondria integrate a variety of signals. Mitochondrial dysfunction and disruption of circadian rhythms are observed in neurodegenerative diseases and during aging. However, how mitochondrial dysfunction influences circadian rhythm is largely unknown. Here, we report that Drosophila prune (pn), which localizes to the mitochondrial matrix, is involved in the regulation of circadian rhythm in circadian cells. Deletion of pn in flies caused decreased expression of mitochondrial transcription factor TFAM and reductions in levels of mitochondrial DNA, which resulted in mitochondrial dysfunction and decreases in the amplitude of the endogenous clock. In addition, we showed that depletion of mtDNA by overexpression of a mitochondrially targeted restriction enzyme mitoXhoI also decreased the robustness of circadian rhythms. Our work demonstrates that there maybe a mechanism underlying the mitochondrial dysfunction and impairment in circadian rhythm.